Cloud Computing Using AWS: An Analysis - Sinha, Prashansa (Indian Journal of Computer Science, 2020)
Cloud computing has become a driving innovation, it has become so popular and successful that everyone is stepping ahead towards Cloud. Today Cloud computing is the foremost demand of companies as it benefits their growth. With Cloud computing, new businesses witnessed immense success by locating their services and data on the internet without depending on any of physical operations. This independency and trend have inspired many eminent companies such as Netflix, Salesforce, and Amazon to move towards Cloud-based infrastructure. Cloud computing also refers to a set of policies, technologies and controls used to protect data, applications, and infrastructure. There is a wide range of Cloud service providing companies and platforms in which Amazon Web Services (AWS) and Microsoft Azure are regarded as the leading Infrastructure as a Service (IaaS) Cloud. In this paper, AWS and Microsoft Azure are compared and points why AWS is at peak or better than others are highlighted. The aim of this paper is to present an insightful description of Cloud computing, its characteristics, and Cloud computing models. This paper also describes various AWS services and shows its uniqueness by comparing it with other Clouds. It also explores certain benefits of Cloud computing using AWS over traditional IT service environments including how it is helping education industry to evolve and how it is transforming our lifestyle for better and easy access to things. This article gives an overview of the benefits of AWS.